Lessons from a career in space physics - Rostoker, Gordon (Frontiers in Astronomy and Space Sciences, 2022)
Frameworks for describing magnetospheric substorms are as good as the data on which they are based. While disturbances in the ionosphere are well described by existing data bases, the plasma and field data acquired by satellites in the magnetosphere are sparse and unable to lend an element of uniqueness to any model for substorm activity. This paper describes the voyage of discovery experienced by the author from the leadup to his career to the time of his retirement. Perhaps it will provide young scientists with a sense of how space physics developed and what needs to be done before the solar wind-magnetosphere-ionosphere interaction becomes fully understood.